1985
DOI: 10.1007/bf00261568
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hormone therapy on peripheral blood leukocytic subset distribution in stage D prostatic cancer patients

Abstract: The distribution of mononuclear cell types found in the peripheral blood of patients bearing carcinoma of the prostate were compared by stage and to a control group using monoclonal antibody techniques. Patients with lower stage disease (A, B) had no significant alteration in subset distribution when compared to a control group, while those with higher stage disease (D) had significant deviations. Stage D patients had a decreased representation of helper-inducer T cells and an increased representation of suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Urologic tumors, involving those of the prostate, transitional cells of the bladder, and granular cells of the kidney are immunogenic, provoking lymphocytic infiltration or granulomatous reactions [ 13. Previous reports from our laboratory have shown that patients bearing prostatic cancers have elevated levels of circulating immune complexes [2], specific cell-mediated immunity against homologous tumor extracts [3], and peripheral blood leukocytic subset alterations, which are in part reversible following hormonal therapy [4]. Similar alterations in leukocytic subset distributions have also been identified in other urologic tumors such as renal carcinoma, also in part reversed by therapy [20].…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Urologic tumors, involving those of the prostate, transitional cells of the bladder, and granular cells of the kidney are immunogenic, provoking lymphocytic infiltration or granulomatous reactions [ 13. Previous reports from our laboratory have shown that patients bearing prostatic cancers have elevated levels of circulating immune complexes [2], specific cell-mediated immunity against homologous tumor extracts [3], and peripheral blood leukocytic subset alterations, which are in part reversible following hormonal therapy [4]. Similar alterations in leukocytic subset distributions have also been identified in other urologic tumors such as renal carcinoma, also in part reversed by therapy [20].…”
Section: Discussionmentioning
confidence: 54%
“…This is particularly evident in Table I and less clearly so in Table 11. In studies of leukocytic subset distributions within peripheral blood of humans bearing stage D prostate cancer, it was the suppressor-cytotoxic T cells that appeared most sensitive to tumor presence [4]. Cyclophosphamide in this system reduced all T cell populations in both tumor and non-tumor-bearing animals.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations